PENGARUH KUALITAS PELAYANAN, REPUTASI, DAN HARGA PREMI ASURANSI TERHADAP KEPUTUSAN PEMEGANG POLIS DALAM MEMILIH ASURANSI BUMIPUTERA 1912 (STUDI KASUS PADA ASURANSI JIWA BERSAMA BUMIPUTERA 1912 KANTOR CABANG ASKUM SEMARANG) - Intan Hidayatillah; Sri Suryoko; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2015)
This research was motivated by the phenomenon of the development of services that controls 72 per cent and 67 per cent of gross domestic product ( GDP ) in developed countries around the world ( Christopher Lovelock , 2007: 7 ) . One of the services needed by society today is insurance . This is why the competition between insurance companies is very sharp which is characterized by the emergence of new insurance companies , so the competition will be intense . Life Insurance is one of the set of branches of AJB Bumiputera 1912 that provides insurance services to a group or collection and also always give the best to the policyholders . Bumiputera prove that the policyholder satisfaction on the product by obtaining Indonesian Customer Satisfaction Award ( ICSA ) , Top Brand Award , and gaining recognition as a leading insurance company in Indonesia for 10 consecutive years from 2003 until 2013 ( Company Profile AJB Bumiputera 1912 ) , but the achievement of policy from 2010 to 2013 never reached the target .                    The purpose of this study was to determine the effect of quality of service , reputation and price premiums to the policyholder 's decision in choosing the group life insurance products ( askum ) AJB Bumiputera 1912 Semarang . This type of research is explanatory research , with data collection through questionnaires and interviews . Sampling technique using purposive sampling technique . The sample in this study amounted to 76 respondents who are policyholders AJB Bumiputera 1912 Askum branch office in Semarang . This study used quantitative analysis techniques . Quantitative analysis using validity , reliability test , correlation coefficient , simple and multiple regression analysis , the coefficient of determination , tests of significance ( t test and F test ) with rock SPSS for windows version 20.0 .The results of this study indicate that the quality of service ( X1 ) , reputation ( X2 ) and the price premium ( X3 ) partially and simultaneously influence the purchase decision ( Y ) .                    Based on the research results , the researchers suggested that the company further improve the quality of care in the form of making the system claims handling standards , maintaining product quality and post various Bumiputera achievement on the internet in order to raise the reputation of the company as well as providing a policy to lower the insurance money so that premium rates can be quite low but still with good service and benefits are balanced so as to increase group life insurance purchasing decision AJB Bumiputera 1912 Semarang.